Block identification and stability analysis of underground stope with multi-working face - Minsi Zhang; Chenlong Tie; Bin Wang; Yong Yang; Chen Wang; Wenpan Sun; Jingxiao Xia; Xin Zhou (PLoS ONE, 2026)
The stability analysis of multi-working face stopes presents significant challenges due to complex concave geometries that limit conventional block theory applications. This study proposes a novel methodology in which rock mass models are constructed through the combination of convex sub-regions, enabling the application of traditional cutting algorithms. Block identification is achieved through discontinuity contraction and sub-region merging, effectively accounting for finite discontinuity sizes. The proposed method was implemented into the software GeoSMA-3D and applied to a shallow-buried metal mine stope. The analysis successfully identified all independent blocks, including key blocks critical for stability. The results demonstrate that excavation disturbances lead to an increase in discontinuity persistence, subsequently causing a notable rise in the number of key blocks. The integration of random discontinuities with deterministic features revealed a total of 205 key blocks, 60% of which involved the deterministic discontinuities. These key blocks have a maximum volume of 5.37 m³ and are predominantly distributed along the deterministic discontinuities. The results demonstrate the precision and efficacy of the proposed method for analyzing complex, multi-face excavations. This work provides a robust technical framework for the stability assessment of surrounding rock in mining stopes.